Pancreaticobiliary Cancers and Aeromonas Isolates Carrying Type Ⅲ Secretion System Genes ascF-ascG Are Associated With Increased Mortality: An Analysis of 164 Aeromonas Infection Episodes in Southern Taiwan - Chen, Ying-Wen; Su, Shu-Li; Li, Chia-Wen; Tsai, Chin-Shiang; Lo, Ching-Lung; Syue, Ling-Shan; Li, Min-Chi; Lee, Ching-Chi; Lee, Nan-Yao; Ko, Wen-Chien; Chen, Po-Lin (Frontiers in Cellular and Infection Microbiology, 2021)
This prospective study aimed to investigate the clinical and microbiological characteristics of different Aeromonas species. Clinical isolates of Aeromonas species between 2016 to 2018 were collected in a university hospital in southern Taiwan. The species was determined by rpoD or gyrB sequencing. A total of 222 Aeromonas isolates from 160 patients in 164 episodes were identified. The crude in-hospital mortality was 17.2%. The most frequently isolated species was Aeromonas veronii (30.6%), followed by A. caviae (24.8%), A. hydrophila (23%), and A. dhakensis (16.7%). The major clinical manifestations were primary bacteremia (31.1%), skin and soft tissue infection (22.6%), and biliary tract infection (18.3%). The most common underlying diseases were malignancy (45.1%), diabetes mellitus (27.4%), and liver cirrhosis or chronic hepatitis (26.2%). A. hydrophila and A. dhakensis predominated in the skin and soft tissue infection (p<0.0001), whereas A. vernoii and A. caviae prevailed in primary bacteremia and biliary tract infections (p=0.012). Pneumonia, malignancy, and ascF-ascG genotype were independent factors associated with mortality. Ertapenem susceptibility was decreased in A. sobria (42.9%), A. veronii (66.7%), A. dhakensis (73%), and A. hydrophila (84.3%). Cefotaxime resistance was found in 30.9% of A. caviae and 18.9% of A. dhakensis isolates, much more prevalent than the other species. The metallo-β-lactamase blaCphA was almost invariably present in A. dhakensis, A. hydrophila, and A. veronii (100%, 100% and 89.9%, respectively). Amp-C β-lactamases such as blaMOX and blaAQU-1 were identified in all A. caviae and 91.9% of A. dhakensis isolates. Cefepime, fluoroquinolones and tigecycline showed good in vitro activity against aeromonads.